Relationship between the degree of myocardial damage according to contrast-enhanced cardiac magnetic resonance imaging and laboratory data in patients with acute myocardial infarction - O. V. Mochula; A. S. Sulejmanova; A. E. Sukhareva; V. V. Ryabov; K. V. Zavadovsky (Российский кардиологический журнал, 2022)
Aim. To evaluate the information value of a complex of clinical and biochemical parameters of myocardial damage in predicting the development of transmural myocardial damage according to magnetic resonance imaging (MRI) in patients with acute myocardial infarction (AMI).Material and methods. The study included patients admitted to the emergency cardiology department with acute coronary syndrome. All patients underwent invasive coronary angiography, laboratory tests, and dynamic determination of cardiac biomarkers. In the interval of 6,1±4 days from admission to the hospital, patients underwent contrast-enhanced cardiac MRI. According to the pattern of delayed contrast enhancement, patients were divided into two groups: with a transmural and subendocardial pattern.Results. The mean age of patients was 62,5±10,5 years, while 27 (71,1%) had ST-segment elevation AMI. Among the risk factors for coronary artery disease, dyslipidemia (89,5%), hypertension (68,4%), and smoking (57,9%) were the most common. Creatine phosphokinase-MB (CPK-MB), serum high-sensitivity cardiac troponin I (cTnI) and C-reactive protein (CRP) values after 24 h were significantly higher in patients with transmural hyperenhancement. Moderate positive relationship was found between the global size of left ventricular (LV) damage according to MRI data and the levels of CPK-MB after 24 h and 4 days, as well as with CRP after 24 h, 4 and 7 days, and cTnI level after 24 h and 4 days. In the group of patients with transmural pattern, the global size of LV damage was significantly higher. Patients of this group were characterized by higher prevalence of microvascular obstruction. In a univariate regression analysis, there were following significant predictors of transmural myocardial damage: CPK-MB after 4 days (p=0,023) and ST segment elevation (p=0,029). Multivariate regression analysis showed that the only independent predictor of transmural myocardial damage was an increase in CPKMB after 4 days (p=0,023).Conclusion. An independent predictor of LV transmural damage in AMI was an elevated level of CPK-MB after 4 days. However, this laboratory marker had unsatisfactory information completeness and predictive quality. In this regard, cardiac MRI in patients with AMI, compared with the standard clinical assessment, can be considered preferable for assessing the depth of myocardial damage, risk stratification, and prognosis.